Prenatal and neonatal variables associated with enamel hypoplasia in deciduous teeth in low birth weight preterm infants - Kátia Maria Dmytraczenko Franco; Sérgio Roberto Peres Line; Maria Valeriana Leme de Moura-Ribeiro (University of São Paulo, 2007)
This study investigated possible prenatal and neonatal variables that may influence the prevalence of tooth enamel hypoplasia in preterm and low birth weight children (LBW) and a matched control group of term children with normal birth weight (NBW). The study sample consisted of 61 children born preterm and with LBW examined at 18-34 months of age. The control group was formed by 61 infants born full term and with NBW examined at 31-35 months of age. All children were born at the Center of Integrated Attention of Women's Health (CAISM-UNICAMP). FDI criteria were followed for dental examination. Medical data was collected retrospectively from hospital records. Among preterms, 57.4% had some type of developmental defects of enamel (DDE), 52.5 % had opacities and 21.3 % presented hypoplasia. Among full-term children, 24.6% presented DDE, 24.6% had opacities and 3.3% had hypoplasia. LBW preterm infants presented a higher prevalence of hypoplasia than NBW controls. The deciduous teeth most affected by hypoplasia were maxillary incisors. There was no significant association with prenatal variables; among neonatal variables there was a significant association with respiratory distress syndrome and neurological examination at discharge with an altered result.